Evaluation of the MicroRNA184 Levels in Women with Miscarriage Association with Toxoplasmosis, Rubella, and CMV Infections - A. Mahmood, Sarah; Muhsin, Salwa S.; Faraj, Rawah A. (HAYATI Journal of Biosciences, 2026)
MiR-184 plays a significant regulatory role in immunity during pregnancy. Its dysregulation in toxoplasmosis and rubella infection is strongly associated with increased risk of abortion . Further clinical studies are needed to validate miR-184 as a diagnostic marker and therapeutic target in pregnancy complications. One hundred specimens of blood were taken from the miscarriage ladies, with age ranges between 15 and 50 years, who were complaining of TORCH infections. The findings showed that the age range group (